Lack of EULAR/ERA-EDTA response at 1 year predicts poor long-term renal outcome in patients with lupus nephritis. Issue 8 (5th June 2020) - Moroni, Gabriella; Gatto, Mariele; Tamborini, Francesco; Quaglini, Silvana; Radice, Francesca; Saccon, Francesca; Frontini, Giulia; Alberici, Federico; Sacchi, Lucia; Binda, Valentina; Trezzi, Barbara; Vaglio, Augusto; et al.
Abstract : Objectives: Short-term predictive endpoints of chronic kidney disease (CKD) are needed in lupus nephritis (LN). We tested response to therapy at 1 year. Methods: We considered patients with LN who underwent renal biopsy followed by induction therapy between January 1970 and December 2016. LN was assessed using the International Society of Nephrology/Renal Pathology Society (2003) criteria and the National Institute of Health (NIH) activity and chronicity index. The renal outcome was CKD. Response was defined according to EULAR/European League Against Rheumatism/European Renal Association-European Dialysis and Transplant Association (EULAR/ERA-EDTA) recommendations: complete: proteinuria <0.5 g/24 hours, (near) normal estimated glomerular filtration rate (eGFR); partial: ≥50% proteinuria reduction to subnephrotic levels, (near) normal eGFR; and no response: all the other cases. Logistic regression analysis was employed for 12-month response and Cox regression for CKD prediction. Results: We studied 381 patients (90.5% Caucasians). After 12-month therapy, 58%, 26% and 16% of patients achieved complete, partial and no response, respectively, according to EULAR/ERA-EDTA. During a median follow-up of 10.7 (IQR: 4.97–18.80) years, 53 patients developed CKD. At 15 years, CKD-free survival rate was 95.2%, 87.6% and 55.4% in patients with complete, partial and no response at 12 months, respectively (p<0.0001). CKD-free survival rates did not differ between complete and partial responders (p=0.067). Serum creatinine (HR: 1.485, 95% CI 1.276 to 1.625), eGFR (HR 0.967, 95% CI 0.957 to 0.977) and proteinuria at 12 months (HR 1.234, 95% CI 1.111 to 1.379) were associated with CKD, yet no reliable cut-offs were identified on the receiver operating characteristic curve. In multivariable analysis, no EULAR/ERA-EDTA response at 12 months (HR 5.165, 95% CI 2.770 to 7.628), low C4 (HR 1.053, 95% CI 1.019 to 1.089) and persistent arterial hypertension (HR 3.154, 95% CI 1.500 to 4.547) independently predicted CKD. Conclusions: Lack of EULAR/ERA-EDTA response at 12 months predicts CKD.